TGFβ signaling hyperactivation-induced tumorigenicity during the derivation of neural progenitors from mouse ESCs. (20th April 2018) - Yang, Xianfa; Wang, Ran; Wang, Xiongjun; Cai, Guoqing; Qian, Yun; Feng, Su; Tan, Fangzhi; Chen, Kun; Tang, Ke; Huang, Xingxu; Jing, Naihe; Qiao, Yunbo
Abstract: Clinical therapies of pluripotent stem cells (PSCs)-based transplantation have been hindered by frequent development of teratomas or tumors in animal models and clinical patients. Therefore, clarifying the mechanism of carcinogenesis in stem cell therapy is of great importance for reducing the risk of tumorigenicity. Here we differentiate Oct4-GFP mouse embryonic stem cells (mESCs) into neural progenitor cells (NPCs) and find that a minority of Oct4+ cells are continuously sustained at Oct4+ state. These cells can be enriched and proliferated in a standard ESC medium. Interestingly, the differentiation potential of these enriched cells is tightly restricted with much higher tumorigenic activity, which are thus defined as differentiation-resistant ESCs (DR-ESCs). Transcriptomic and epigenomic analyses show that DR-ESCs are characterized by primordial germ cell-like gene signatures ( Dazl, Rec8, Stra8, Blimp1, etc.) and specific epigenetic patterns distinct from mESCs. Moreover, the DR-ESCs possess germ cell potential to generate Sycp3+ haploid cells and are able to reside in sperm-free spermaduct induced by busulfan. Finally, we find that TGFβ signaling is overactivated in DR-ESCs, and inhibition of TGFβ signaling eliminates the tumorigenicity of mESC-derived NPCs by inducing the full differentiation of DR-ESCs. These data demonstrate that these TGFβ-hyperactivated germ cell-like DR-ESCs are the main contributor for the tumorigenicity of ESCs-derived target cell therapy and that inhibition of TGFβ signaling in ESC-derived NPC transplantation could drastically reduce the risk of tumor development.